Studying The Determinants of Intention To Use Tokopedia for SMEs Agribusiness Products Purchase - Lufebrina Dorma Uli Manalu; Irman Hermadi; Joko Ratono (School of Business, IPB University (SB-IPB), 2020)
Toko Laurike located in Bogor Regency, is a member of the small-medium enterprises (SMEs) group. It produces Virgin Coconut Oil (VCO) and sells its products through several e-marketplaces, namely Tokopedia, Bukalapak, and Elevenia. Among these e-marketplaces, Tokopedia sells product from Toko Laurike more than Bukalapak or Elevenia. This research aims to examine the factors that determine Consumers’ intention to use of Tokopedia specifically for SMEs’ food agribusiness products in the form of liquid and gel. This research also analyzed the pattern of design and security perceived ease of use and perceived usefulness. The other purpose is analyzing the contribution of security, perceived ease of use, perceived usefulness on consumers’ intention to use. Data analysis tool using structural equation modeling - partial least squares (SEM-PLS) based on stimulus theoretical framework technology acceptance model (STF-TAM). The study involved Tokopedia’s users who making purchasing for SMEs food agribusiness products in the form of liquid and gel. The 71 samples were collected. The results showed that perceived ease of use is most influencer among these factors. Design and security associated with perceived ease of use. Security was not associated with consumers’ intention to use. The result can be used by Laurike to enhance e-commerce performance. Keywords: Laurike’s e-commerce, SMEs, SEM-PLS, STF-TAM, Tokopedia